VAT and Tax Credits: A Way to Eliminate Tax-Evasive Use of Transfer Prices? - Tomáš Buus; Jaroslav Brada (European Financial and Accounting Journal, 2010)
In this paper we compare income taxes to VAT and tax credits to tax deductions in terms of their ability to distort factor prices, provide fair taxation, avoid tax-evasive transfer pricing and induce Pareto improvement of tax policies. On the base of theoretical discussion and thought experiments we conclude that VAT is due to its nature superior regarding these requirements. We also have found out that a wider use of tax credits within VAT would be useable to prevent profit shifting. Some adjustments of VAT compared to current practice are needed to achieve the best results. More rigorous proofs, both theoretical and empirical are needed.
Keywords: D21; D29; G39; 650; Tax credits; VAT; Transfer prices; Multinational enterprises; Pareto optimum